Researcb on Solutions and Key Tecbnologies of Social Communication Service Based on TV - Jianting Han; Zhengkai Zhang; Wenda Ying; Hua Ding (Dianxin kexue)
The strategy of social video communication service based on TV was discussed and introduced,and system deployment solutions in current network were proposed.For good social experience and communication quality,the key technologies were analyzed,including screen adaptation,video overlay,real time video codec and video quality self-adaption etc.At last,by laboratory testing,the whole solutions can be applied in current network feasibly.